2017
DOI: 10.2319/022416-161.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the coatings covering esthetic orthodontic archwires and their influence on the bending and frictional properties

Abstract: Orthodontic coated wires with small inner alloy cores withstand less force than expected and may be unsuitable for establishing sufficient tooth movement. The frictional force of coated wires is influenced by total cross-section diameter, inner core diameter, nanohardness, nanoelastic modulus, and elastic modulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 18 publications
(43 reference statements)
3
33
0
1
Order By: Relevance
“…However, only DLC-2 produced significantly lower frictional force than the non-coated case in the drawing-friction test with a 10 • positioning of the bracket under the wet condition. This was attributed to partial rupture of the coating of DLC-1, causing increasing wire-binding at the edge of the bracket [34], thereby increasing the frictional force. Crack initiation and ruptured coating regions were not observed for DLC-2, which suggested that the DLC-2 coating had good flexibility as a functionally-graded material with outstanding adhesion to the orthodontic stainless steel substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, only DLC-2 produced significantly lower frictional force than the non-coated case in the drawing-friction test with a 10 • positioning of the bracket under the wet condition. This was attributed to partial rupture of the coating of DLC-1, causing increasing wire-binding at the edge of the bracket [34], thereby increasing the frictional force. Crack initiation and ruptured coating regions were not observed for DLC-2, which suggested that the DLC-2 coating had good flexibility as a functionally-graded material with outstanding adhesion to the orthodontic stainless steel substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive load scratch test used in the present study showed that the BG-coated specimens (DC 15 V) displayed significantly higher frictional forces than the other BG-coated specimens (DC 10 V; AC 10 and 15 V), although the other BG-coated specimens produced slightly higher frictional forces compared with the non-coated stainless steel specimen. The stainless steel wire alloy generally generates lower levels of frictional resistance than coated wires [15], and the BG-coated specimens, in some conditions, displayed frictional performance that was similar to that of the non-coated stainless steel specimens. Thus, the BG coating can likely provide acceptable clinical frictional characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The frictional properties are attributed to multiple factors, such as surface roughness, hardness, elastic modulus, and the cross-sectional dimensions of the orthodontic wires and brackets [37,38]. A recent study reported that commercially available esthetic coating wire influences the frictional properties [15] and the esthetic polymer coating may increase the frictional resistance due to increased wire-binding at the edge of the bracket. The progressive load scratch test used in the present study showed that the BG-coated specimens (DC 15 V) displayed significantly higher frictional forces than the other BG-coated specimens (DC 10 V; AC 10 and 15 V), although the other BG-coated specimens produced slightly higher frictional forces compared with the non-coated stainless steel specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, resin-coated wires showed friction between the bracket and the wire that was equivalent to or higher than that of the conventional metal wire. 8,9 Therefore, development of an orthodontic wire that has a certain esthetic benefit with friction equal to or less than that of a conventional metal wire would be ideal to meet the current clinical demand.…”
Section: Introductionmentioning
confidence: 99%